2018
DOI: 10.1063/1.5012562
|View full text |Cite
|
Sign up to set email alerts
|

An analytic investigation for the edge effect on mechanical properties of graphene nanoribbons

Abstract: We derive analytical expressions for the Young's modulus and the Poisson's ratio of the graphene nanoribbon, in which free edges are warped by the compressive edge stress. Our analytical formulas explicitly illustrate the reduction of the Young's modulus by the warped free edges, leading to the obvious width dependence for the Young's modulus of the graphene nanoribbon. The Poisson's ratio is also reduced by the warped free edges, and negative Poisson's ratio can be achieved in the graphene nanoribbon with an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Those results suggest that the elastic properties are insensitive to the size of Gr membrane. Zhao et al [40] and Han et al [26] reported that the size effect on Young's modulus and Poisson's ratio can be negligible when the diagonal length and width of Gr nanoribbon beyond 10 nm and 2 nm, respectively. Furthermore, in order to explore the influence of edge effect and interface confinement on the adhesion properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those results suggest that the elastic properties are insensitive to the size of Gr membrane. Zhao et al [40] and Han et al [26] reported that the size effect on Young's modulus and Poisson's ratio can be negligible when the diagonal length and width of Gr nanoribbon beyond 10 nm and 2 nm, respectively. Furthermore, in order to explore the influence of edge effect and interface confinement on the adhesion properties.…”
Section: Resultsmentioning
confidence: 99%
“…Even more than that, the interface effect can also disturb the orientation of πand σ-orbital and simultaneously induce the in-plane and out-of-plane strain to be taken place, resulting in the change the mechanical properties of Gr such as Young's modulus and Poisson's ratio [23,24]. Especially, as the unsaturated dangling bonds in the edge carbon atoms, the strong bonds would be formed in Gr/substrate system and the mechanical properties of the Gr depend on the edge chirality [25,26]. In this case, when decreasing the area or size of Gr, the strain would be redistributed in the Gr/substrate systems due to the enhancement of SVR, resulting in the change of the interaction and adhesion energy in various edge chirality of Gr.…”
Section: Introductionmentioning
confidence: 99%